Adverse Events Following Immunization (AEFI) in Nursing Science Program Sam Ratulangi University Students Based on the Type of COVID-19 Vaccine - Ahmad, Musfirah; Natalia, Adriani; Wijaya, Nur Anindhita Kurniawaty (Faculty of Nursing, Universitas Hasanuddin, 2023)
Aims: The purpose of this study is to describe Adverse Events Following Immunization (AEFI) among Nursing Science Program Sam Ratulangi University students based on the type of Covid-19 vaccination that they received. Methods: This investigation was conducted using a descriptive retrospective study approach. Purposive sampling was utilized to choose the sample for this study, which included 183 undergraduate students in the Nursing Science Program Sam Ratulangi University. Results: After receiving the first dosage of the vaccination, Nursing Science Program Sam Ratulangi University students most frequently reported headache and muscle pain (30.4%), followed by pain and weakness in the injected arm (20.8%), and swelling at the injection site (26%). Additionally, there were students who received doses 1, 2, and 3 of the vaccination who did not exhibit any side effects. These students were 45 at dosage I, 73 at dose II, and 45 at dose III. At dose 1, the majority of Nursing Science Program Sam Ratulangi University students (73.2%) exhibited AEFI symptoms for less than a day, at doses II and III, 43.7% and 31.1%, respectively, reported experiencing symptoms for one to three days. Conclusion: Based on the research that has been done, it can be said that Nursing Science Program Sam Ratulangi University students only encounter mild AEFI symptoms. So it is hoped that the general public or students won't have to worry about the COVID 19 vaccine causing AEFI symptoms and can get vaccinated right away to strengthen their immunity against the virus.